Ultrasound pre-treatment enhances the carrot drying and rehydration - Ricce C. (2016)
The authors are grateful to the São Paulo Research Foundation (FAPESP, Brazil) for funding the project n° 2014/16998-3 and the National Council for Scientific and Technological Development (CNPq, Brazil) for funding the project n° 401004/2014-7. The authors are also grateful to Cienciactiva for the A.C. Miano Ph.D. (CONCYTEC, Peru; Contract 272-2015-FONDECYT) and M.L. Rojas Ph.D. (CONCYTEC, Peru; Contract 087-2016-FONDECYT) scholarships, from the “Consejo Nacional de Ciencia, Tecnología e Inovación Tecnológica”.